(untitled) (Panacea Journal of Medical Sciences, 2024)
Background and Objectives: Studying human subjects is the focus of anthropology. As a result of a differential growth process, facial morphology varies between individuals and helps us to identify them. In this study, the variation between Zygion to mention distance in Gurkha and Kumauni ethnic groups of the Dehradun, Uttarakhand, area of India, was examined with the help of anthropometric tools. Materials and Methods: In present study, there are two hundred subjects including hundred males and hundred females from ethnic groups of Gurkha and Kumauni ethnic groups, born and gowned from their actual remote areas of Uttarakhand, age group selected from 20 years and to 35 years living subjects. The study sample comprised of random selection from their remote areas. The distance between two bony landmarks is known as the Zygion to mention distance. Result: The correlation is much similar to the threshold value. Its mean that the parameter; Zygion to Mention distance, it is the appropriate anthropometric parameter for the identification of ethnic groups of Gurkha and Kumauni of Uttarakhand region of India. Discussion and Conclusion: In case of both Gurkha genders the statistical data indicates that the result is showing significance. In Kumauni male and female genders, the statistical data indicates that the result is statistically highly significant. Thus statistic indicates that the correlation is much again similar to the threshold value in case of both ethnic groups.